KONSEP DASAR PENDIDIKAN AKHLAK ANAK USIA DINI - Bahtiar Siregar (Jurnal At-Tabayyun, 2019)
Education will always be something that is important for everyone. He is a sign of the progress or decline of a nation. History has noted that advanced civilizations are civilizations that pay attention to the educational aspects of their society. The fall and fall of the great civilization also began with a lack of support and encouragement to the world of education. Character education has not been fully used as a reference to overcome the problems of education in this country. Because it only focuses on human values ​​and norms. Only print humans who know the good (knowing the good), love the good (loving the good), and do good (doing the good) to fellow creatures, but minimal will be the unity of godliness and divinity. Thus, moral education can be said also as Islamic education (ta'dib). A deeper examination of the moral concepts that have been formulated by past Islamic education leaders such as Ibn Miskawaih and Al-Ghazali above shows that the ultimate goal of moral education is the formation of noble moral students, which is nothing but the incarnation of the noble qualities of God in life humans according to their nature.